Pengawasan dalam Pendidikan - saehu abas (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2020)
The world of education is inseparable from the responsibilities of government, parents, and society. Because if education is not approved or there is no responsibility, it is feared that in the future education will be increasingly unclear. However, the role of education supervisors is very supportive, because without the presence of expert supervisors (professionals) it is not possible for educational institutions to run well and have quality. This study uses the Literature Research method. In accordance with the focus discussed, namely